Chocolate Ganaches: Formulation, Processing and Stability in View of the New Production Trends - Lapčíková, Barbora; Lapčík, Lubomír; Valenta, Tomáš; Neuwirth, Vojtěch (Foods (Basel, Switzerland), 2024)
This review aims at the current trends in chocolate ganache production and recipe formulation. Ganache is a blend of chocolate, sugars, dairy, and other ingredients commonly used to fill pralines, pastries, etc. In spite of ganache's popularity in the food industry, a comprehensive review focused on the application of functional substances and ganache processing has not been discussed in the scientific literature. This review addresses the new ways of applying special ingredients, such as vegetable fats and seeds, flavor infusions, oleogels, hemp products, etc., which can be added to the ganache matrix to achieve desirable properties. In particular, the application of sterols and sterol esters as functional substances of oleogels seems to be a very promising method, enhancing the ganache fat profile. The elevated caloric content that is characteristic of ganache can be substantially attenuated through the application of hydrocolloids and/or fruit-based components, thereby offering the potential for caloric reduction without compromising on taste. The various alterations to ganache formulations by the application of natural substances offer a large base for the development of novel ganache variants and relevant food products.
Keywords: chocolate; hydrocolloids; recipe formulation; ganache; oleogels; pralines; emulsion; ganache processing